Global Warming and Central Asia: Political and Social Dimensions - Kuldip Singh and Nayanika Singh (2011)
Even though a universal concern, the impact of global warming on different regions of the world is far from even in terms of spread, consequences and costs. Some regions such as Central Asia are its victims on a particularly acute level. Much of it a part of former Soviet Union, Central Asia had to pay a heavy price for the rapid but reckless industrialization and nuclear testing undertaken by the former Superpower. Although it now constitutes several independent states, the region has to bear the fallout of China‟s equally ambitious industrial and military buildup. This paper suggests how the consequences of climate change have set the region on a course of internal strife